2019
DOI: 10.1017/s2045796019000696
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterning and correlates of self-harm in Manchester, England

Abstract: Aims To investigate the spatial distribution of self-harm incidence rates, their socioeconomic correlates and sex/age differences using data on self-harm presentations to emergency departments from The Manchester Self-Harm Project (2003–2013). Methods Smoothed standardised incidence ratios for index self-harm episodes (n = 14 771) and their associations with area-level socioeconomic factors across 258 small areas (median population size = 1470) in the City of Manchester municipality were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…The results regarding socioeconomic disadvantage are consistent with an established body of research demonstrating a relationship between disadvantage and poorer mental health, including increased self-harm (Cairns et al, 2017;Carr et al, 2016;Griffin et al, 2019;Hawton et al, 2001;Lin et al, 2020;Lodebo et al, 2017;O'Farrell et al, 2014). The effect sizes observed in the present study suggests that disadvantage has a substantive relationship with self-harm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results regarding socioeconomic disadvantage are consistent with an established body of research demonstrating a relationship between disadvantage and poorer mental health, including increased self-harm (Cairns et al, 2017;Carr et al, 2016;Griffin et al, 2019;Hawton et al, 2001;Lin et al, 2020;Lodebo et al, 2017;O'Farrell et al, 2014). The effect sizes observed in the present study suggests that disadvantage has a substantive relationship with self-harm.…”
Section: Discussionsupporting
confidence: 89%
“…Parental socioeconomic position (based on income and education) was associated with child self-harm rates in Sweden (Lodebo et al, 2017). Studies in the UK and Ireland have further demonstrated that area-level disadvantage (including specific indicators such as unemployment) has a consistent and substantive association with self-harm rates (Carr et al, 2016;Griffin et al, 2019;Hawton et al, 2001;Lin et al, 2020;O'Farrell et al, 2014). These studies rely on rates of self-harm based on people presenting to health services, and so miss instances of self-harm that do not result in health service contact.…”
Section: Does Neighbourhood Identification Buffer Against the Effects...mentioning
confidence: 97%
“…The burden of adult responsibilities such as economic independence, employment, and family obligations are more apparent in young adults (Benson & Furstenberg Jr, 2006). A failure to fulfill these roles will result in feelings of economic failure and self-harm impulses (Lin, et al, 2020 ). The loss of young adults, who play a significant role in economic activities, is a tremendous loss for society.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies in a 2015 systematic review [8] have suggested that self-harm rates may no longer be raised in South Asian women but two studies, one in Manchester, Derby and Oxford [9] and the other in London [10] have suggested they may be raised in young Black women. Conversely, recent area-level studies in South East London [11] and Manchester [12] have suggested that rates of selfharm may be lower in areas with higher non-White British populations.…”
Section: Introductionmentioning
confidence: 88%